A study revealing volatile aroma produced by Pediococcus pentosaceus in dough fermentation - Gong, Yunxia (Food Sci Nutr, 2020)
Pediococcus pentosaceus is important probiotics in Chinese Laomian. Its role in meat and fermented vegetable has been largely demonstrated, but few studies have investigated the role of P. pentosaceus in Chinese Laomian. For this purpose, we simulated Laomian fermentation using Saccharomyces cerevisiae and P. pentosaceus. Volatile aroma was detected by headspace solid‐phase microextraction gas–chromatography‐mass spectrometry. Real‐time fluorescent quantitative polymerase chain reaction was used to determine dynamic growth of S. cerevisiae and P. pentosaceus in fermentation. Extracellular proteins were analyzed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis. Folin–Ciocalteu method was used to detect extracellular protease activity in different pH values. Owing to addition of P. pentosaceus, the types and contents of esters increase, the relative contents of acetic acid hexyl ester, formic acid octyl ester, and heptanoic acid ethyl ester rise obliviously; especially, the relative content of hexanoic acid ethyl ester was highly correlated with P. pentosaceus by increasing 20.61%. As the gel electrophoresis results display, due to mixed fermentation of S. cerevisiae and P. pentosaceus, the 25k Da and 51k Da proteins expression quantity of P. pentosaceus clearly increased. Under neutral and alkaline culture conditions, the extracellular protease activity of P. pentosaceus is higher. This research benefits to gain insight into the fermentation actions of P. pentosaceus in Chinese Laomian.